Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 2000)
Table of Content Modernism and the Stalinist Sublime by Slavoj Zizek Jane & Louise Wilson in the Light of the Gothic Tradition by Gilda Williams James Rosequist Time after Time by John Russell If You Get a Little Red on You, Don’t Wipe It Off by Jeff Koons & James Rosenquist For Jim by Pontus Hulten Horizon Home Sweet Home by Zdenek Felix Rosenquist’s Craft – Painting and the Limits of the Machine by Michael Lobel Stories in T-Shirt Yellow by Constance W. Glenn Sylvie Fleury From Lacan’s Drive to Rodeo Drive – Marketing and Minimalism in Fleury’s Fictional Feminity by Adrian Dannatt Customize by Beatrix Ruf The Nonchalence of Continous Tense-ness by Jutta Koether Jason Rhodes Given 1. The Caprice, 2. The Ferrari by Russell Ferguson Tangential Talk on Rhoades by Eva Meyer-Hermann & Christian Scheidemann The Soluble Fish Is Better Off on the Beach by Roberto Ohrt Henry Bond, Insert Deep Shit – An Interview, Paul Miller & Chris Ofili Susann Walder – Alchemist of the Everyday, Les Infos du Paradis by Anna Helwing Further Adventures in the Two-Party System, Cumulus from America by David Robbins Sacrilege is Positive, Cumulus from Europe by Hilde Teerlinck What’s up with Hans Peter Kuhn by Knut Ebeling
In the work of Jason Rhoades, it looks as if someone had raided a junk store or invaded the domain of the hardware-store fetishist in order to rebuild and explain the universe. At times his enterprise offers an infectiously refreshing antidote for the feeling of helplessness caused by the constant flood of goods that daily threatens to inundate us. Based on the principles of production, distribution and supply, it may seem well ordered, but when Jason Rhoades faces it, he becomes a crazy gardener capable of keeping the onslaught under control and investing it with meaning. In his spectacular exhibition, ”A Perfect World,” shown this winter at the Deichtorhallen in Hamburg, he recreated his father’s garden, while his edition for Parkett—gourds painted by his mother Jackie—coalesces into another playfully cautionary message that the business of creating something and generating meaning quite simply represents a noble human task. Also in this issue an insert by Henry Bond. (editorial by publisher)
boek
Keywords: Fleury, Sylvie; Rosenquist, James; Rhoades, Jason